Let = f (x) 3x + 2 and g(x) = 6x – 7. Find f (x) – g(x).

Responses
3x – 9
–3x + 9
–3x – 5
2x – 1

1 answer

To find f(x) - g(x), we subtract g(x) from f(x).

f(x) - g(x) = (3x + 2) - (6x - 7)

Distribute the negative sign:
f(x) - g(x) = 3x + 2 - 6x + 7

Combine like terms:
f(x) - g(x) = -3x + 9

Therefore, the answer is -3x + 9.
Similar Questions
  1. The random variables X and Y have the joint PMFpX,Y(x,y)={c⋅(x+y)2,0,if x∈{1,2,4} and y∈{1,3},otherwise. All answers in
    1. answers icon 3 answers
  2. Using the expression 56xy + 5 -6x + y/20,find the following:a. Find two sums. b. find the terms of the expression. c. find a
    1. answers icon 1 answer
  3. Solve the following problems by using the binomial formula.a. If n = 4 and p = .10 , find P(x = 3) . b. If n = 7 and p = .80 ,
    1. answers icon 3 answers
  4. Given the function: f(x) = x^2 + 1 / x^2 - 9a)find y and x intercepts b) find the first derivative c) find any critical values
    1. answers icon 0 answers
more similar questions